“Hopeful Gradualness” and Ecclesial Mission - Briola, Lucas (Lumen et Vita, 2015)
On October 13, 2014, the remarkable midterm Relatio post Disceptationem of the 2014 Synod on the Family invoked the legge di gradualità on four occasions. This “law of gradualness” would later be dropped from the final Relatio Synodi, though inarguably its vestiges remained. Simultaneously the locus of disappointment, apprehension, and excitement, the term’s precise meaning remained and continues to remain unclear. Taking the principle to be what Ladislas Orsy would term a “seminal locution” and thus in need of further explication, this paper will examine the law of gradualness through a diachronic lens. It will trace the term’s evolution from its initial emergence around Humanae vitae during the late 1960s and early 1970s, to its reserved acceptance into ecclesiastical parlance in the 1980 Synod on the Family and Familiaris Consortio, to its unique use this past October at the 2014 Synod. It is the contention of this paper that the 2014 Synod marked a new expansion of the term, away from its previously primary, if not exclusive, contentious identification with Humanae vitae. Though maintaining many of its previous connotations, seen in light of Francis’s papacy, the law of gradualness has become fundamentally a foundation and spirituality for the church’s mission to the world. Reflecting God’s own pedagogy revealed most clearly in Jesus Christ, the law of gradualness requires an ecclesial lens of hope. It is a hope that a merciful and authentic encounter with people where they actually are can prompt genuine conversion and growth. The church, as sacrament, is dauntingly tasked to imitate this divine logic that balances the acceptance of the Incarnation with the demands of the Cross. Ultimately then, applying gradualness to the church’s own pilgrim life, this is an eschatological hope that likewise stimulates ongoing ecclesial conversion and so enables authentic growth, accompaniment, dialogue, and mission.